Studying the Presence of Adultery, Fraudulent Imitation and Food Pathogens with in Processed Meat Products (Such As Salami, Sausage, Braised Meat) using DNA Typingand PCR Procedures* (Global Journal of Medical Research, 2015)
Adulteration of meat with cheaper ambiguous meats of different origin during preparation of meat products is a common practice in many countries. Because meat adulteration and mislabeling are illegal and raise many health, religious, cultural and economic issues. In this study, 500 ready to eat raw meat samples (minced meat, lahmacun ingredients, kebap, stew and meatball samples / 100 samples for each type) were collected from different types of plants that were located in Istanbul. The samples were explored if they had different animal originated DNA residues (pork, chicken, cattle, sheep, horse, donkey, cat, dog, mouse, cockroach and house fly) by PCR procedures. According to the results, total of 52 samples were determined as adulterated and different originated animal DNA samples were found (chicken, horse and sheep DNA residues). It was concluded that to apply total quality management and food security systems are very important to decrease the risk factors for both products and the public health.
Keywords: PCR; species identification; ready to eat meat products